Business model grounds and links : towards enterprise architecture perspective - Musulin, Jadranka (Array, 2018)
The business model concept emerged in theory and practice without a consensus onthe understanding of the concept, but it has become a well accepted and usefulconstruct in fields such as strategy, organization, information systems and technology.This paper aims to provide an overview of the research on the use of business modelsfocusing on outstanding works in this field, extracting main converging findingsunburdened of extant lists of specific citations. Following the overview, a comparisonof the seven respective conceptual frameworks of the business model research ispresented. Finally, after determining grounds, the business model concept is linked torelated complex concept – enterprise architecture.